Analisis Efektivitas, Kontribusi Pajak Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (PAD) Serta Tingkat Kemandirian Daerah Kota Pariaman - Randy Primahadi; Rahmat Kurniawan (Universitas Batanghari Jambi, 2021)
This study aims to examine the effectiveness, contribution, local retribution on local revenue and the level of independence of Kota Pariaman. The data analysis method used in this research is quantitative descriptive analysis method. This method is a method of analysis by using the calculation of the financial data obtained to solve problems in accordance with the research objectives. The average level of regional independence in Kota Pariaman during 2014-2018 is 6.09% with a pattern of instructive relationships. It can be seen that the level of regional independence of Kota Pariaman is very low, only around 6% during 2014 to 2018 with a pattern of instructive relationships. This means that the city of Pariaman is very dependent on financial assistance from the center. the role of the central government is more dominant than the independence of the regional government.